Association between exposure to environmental pollutants and increased oral health risks, a comprehensive review - Zhu, Li; Tang, Mengchen; Cai, Yinyin; Wang, Panpan (Frontiers in Public Health, 2025)
The burden of disease and death attributable to environmental pollution is a growing public health challenge worldwide, particularly in developing countries. While the adverse effects of environmental pollution on oral health have garnered increasing attention, a comprehensive and systematic assessment remains lacking. This article delves into the intricate relationship between environmental pollution and oral health, highlighting significant impacts on various aspects such as dental caries, periodontal diseases, oral facial clefts, cancer, as well as other oral diseases. Our results suggested that secondhand smoke, particulate matters (PM) and heavy metals are the most important risk factors affecting oral health. Additional contributors, such as radiation pollutants, electronic cigarette, phthalates, gaseous air pollutants, pesticides, solvents, wood dust, formaldehyde and excessive fluoride were investigated, though evidence for their impacts remains limited and often inconclusive. The review also explores potential mechanisms underlying these impacts, including microorganism, inflammation, oxidative stress, genetic influences, and toxicant exposures from heavy metals and other pollutants. For instance, PM2.5 may contribute to dental caries by disrupting oral pH balance and absorbing heavy metals such as lead and cadmium which have been considered as caries promoting elements. It is also associated with adverse inflammatory responses and tissue damage in periodontal tissues by causing oxidative stress, potentially leading to periodontitis. Drawing on current evidence, it provides a comprehensive analysis of these associations, offering critical insights to guide the development of preventive strategies and public health interventions. The findings highlight the pressing need for future research to validate the causal links between environmental pollution and oral diseases and to unravel the underlying biological mechanisms. Ultimately, greater attention must be directed toward addressing the relationship between environmental pollution and oral diseases, with a focus on pollution control and the reduction of preventable environmental risks to safeguard oral health on a broader scale.